Using prior knowledge, scaffolding, and modelling to teach lessons in economics: three examples from across the curriculum. (1st January 2011) - Claar, Victor V.; Finn, Jane E.
Students often become frustrated with learning economics not because the economics is too hard, but because they try to grasp the economic device, model, or tool being used at the same time they try to understand the economic theory the device is designed to illuminate. As a result, the tool that should aid economic understanding frequently backfires. This paper links three pertinent concepts from the education literature – prior knowledge, scaffolding, and modelling – to teaching economics. After explaining each concept, we supply three strategies designed to leverage each concept for maximum impact. Our examples come from across the curriculum: intermediate macroeconomics, principles of microeconomics and econometrics. We hope that readers will use our ideas and consider further ways of leveraging each concept.